Pengaruh Kekeringan Terhadap Pertumbuhan dan Perkembangan Tanaman Nyamplung (Callophylum inophyllum L.) dan Johar (Cassia florida Vahl.) - , ARIE TRIANI, Drs. Sudjino, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Global warming that occurred in the last few years caused extreme climate change, one of which is drought. To maintain vegetation found in dry areas, it is needed to find alternative plants that are resistant to drought. Some species with high potential adaption to drought condition are Nyamplung (Callophylum inophyllum L.) provenances Baluran and Nyamplung Madura, Johar (Cassia florida Vahl.) provenance Bondowoso and Johar NTT (Nusa Tenggara Timur). The purpose of this research were to examine the growth and development of plants and the response of morphology, physiology, and anatomy of these plants to drought condition, and to determine the adaptive species to drought. This research used drought stress treatment for 10 days, 20 days, 30 days, and 40 days, while control plants were watered very 3 days. Each treatment used 3 replications. Parameters observed were plant height, stem diameter, number of leaves, leaf area, proline levels, plant water content, total dry weight, root dry weight, transpiration rate, stomatal index, root anatomy, anatomy of stem, and leaf anatomy. Physiological data obtained were analyzed using t-test. The results showed that plants responded to drought stress by decreasing plant height, stem diameter, number of leaves, leaf area, root dry weight, total dry weight, water content of plants, transpiration rate, stomata lindex, root cortex thickness, leaf mesophyll thickness, leaf phloem thickness,other wise occurred increasing level of proline, root epidermis thickness, stem xylem diameter, stem cortical thickness and leaf xylem thickness. Nyamplung provenance Baluran more adaptive to drought stress than Nyamplung plant provenance Madura. Johar provenance NTT more adaptive to drought stress than Johar plant provenance Bondowoso. Nyamplung plant was the most adaptive plant to drought stress than Johar plant.